HUBUNGAN ANTARA FAKTOR IBU DENGAN KELUARAN NEONATAL PADA IBU HAMIL DENGAN PRE EKLAMSIA DI RSUD MARGONO SOEKARDJO PURWOKERTO - ., Sumarni (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2018)
Preeclampsia can be bad for both the mother and the fetus it contains. Pregnant women are prone and susceptible to pre eclampsia if they have predisposing factors as follows; Nulipara, multiple pregnancy, Age <20 or> 35 years, History of pre-eclampsia, eclampsia in previous pregnancy, family history of pre-eclampsia, renal disease, hypertension and diabetes mellitus pre-pregnancy, obesity. Objective: To know the relationship between maternal factors with neonatal outcome in pregnant women with pre eclampsia. Methods: This study used descriptive explanatory. The total population of 57 pregnant women with pre-eclampsia in Margono soekardjo Hospital Purwokerto, with random ssmpling Univariate and Bivariate data analysis with menggun. chi square test with degree of confidence p = 0,05. The results showed there was a relationship between parity with asphyxia in pregnant women with pre-eclampsia, and no association between age and history of pre eclampsia with neonatal outcome consisting of LBW, IUFD and neonatal asphyxia. Conclusion There is a relationship between parity with asphyxia neonatorum in pregnant women with pre eclampsia. Keywords: maternal factors, neonatal outcomes, pre eclampsia